Lived Experiences of Parents in Co-Parenting Relationships - Jervin Dinglasan Quicho; France Celine Dominique Yncierto Cabrigas; Marian Ralah Gelera Cañonero; Jofel Marie Mercado Curan (Future Science / FSH-PH Publications, 2026)
This study aims to know the lived experiences of parents in co-parenting relationships, specifically qualitative research that explores their life as someone in a co- parenting relationship. A total of nine (9) parents in co-parenting relationships were interviewed online or face-to-face. A total of six (6) superordinate were generated including ‘Living Through Family Transition,’ Navigating Life Changes and Challenges in Co- parenting.’ ‘Parenting Style and Family Members’ Adjustment in Co-parenting Setup.’ Emotional Connection.’ ‘Views on Formation of Parent and Child Emotional Bond,’ and ‘Proudest Moments and Beneficial Support for Co-parents.’ The study’s findings revealed that participants’ experiences in co-parenting relationships are viewed as challenging and emotionally exhausting, often requiring significant adjustment and emotional resilience. Despite these difficulties many parents emphasized that their co-parenting relationships were less toxic compared to when they were still in relationship with their ex-partner, which allowed them to have a more stable and manageable environment for both them and their children. Aside from these challenges, parents also have positive views of co-parenting with increased cooperation for both parents and having shared commitment with their children’s well-being. A support social activity module was proposed to enhanced and to support the families in co parenting setup relationships in raising a family and child rearing practices.